Cross-cultural technology design creating culture-sensitive technology for local users - Sun, Huatong, 1973- (New York ; Oxford : Oxford University Press, 2012)
This book explores how to create culture-sensitive technology for local users in an increasingly globalized world with rising participatory culture. Illustrated with a cross-cultural study of mobile messaging use, Sun presents an innovative framework integrating action and meaning through a dialogical, cyclical design process to create usable and meaningful technology.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Technology -- Sociological aspects; User-centered system design -- Cross-cultural studies; Human-computer interaction -- Cross-cultural studies; Information technology -- Cross-cultural studies